2017
DOI: 10.1128/iai.00778-16
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate Binding Proteins Regulate Inflammasome Activation in Response to Hyperinjected Yersinia Translocon Components

Abstract: Gram-negative bacterial pathogens utilize virulence-associated secretion systems to inject, or translocate, effector proteins into host cells to manipulate cellular processes and promote bacterial replication. However, translocated bacterial products are sensed by nucleotide binding domain and leucine-rich repeat-containing proteins (NLRs), which trigger the formation of a multiprotein complex called the inflammasome, leading to secretion of interleukin-1 (IL-1) family cytokines, pyroptosis, and control of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 91 publications
0
38
0
Order By: Relevance
“…Some incomplete sets of Yersinia effectors result in increased macrophage death, either via YopE induction of pyroptosis (30,31) or as a result of dysregulated effector and translocon secretion in the absence of YopK (32,41). However, the ΔT3SE::ϩyopHEKM strain expresses both YopM, which prevents YopE-mediated activation of the pyrin inflammasome (30, 31), and YopK, which prevents inflam-masome activation by translocon components (41,42). As expected, therefore, this strain resulted in minimal macrophage death (see Fig.…”
Section: Figmentioning
confidence: 99%
“…Some incomplete sets of Yersinia effectors result in increased macrophage death, either via YopE induction of pyroptosis (30,31) or as a result of dysregulated effector and translocon secretion in the absence of YopK (32,41). However, the ΔT3SE::ϩyopHEKM strain expresses both YopM, which prevents YopE-mediated activation of the pyrin inflammasome (30, 31), and YopK, which prevents inflam-masome activation by translocon components (41,42). As expected, therefore, this strain resulted in minimal macrophage death (see Fig.…”
Section: Figmentioning
confidence: 99%
“…Most importantly, it is not known what drives GBP recruitment to bacteria or their PCVs. Recent work has suggested that in the case of Yersinia pseudotuberculosis or L. pneumophila , GBP recruitment to the PCVs is dependent on the bacterial type‐3 or ‐4 secretion system, respectively, and the recruitment of galectin‐3, a β‐galactoside‐binding protein (Fig. C).…”
Section: Introductionmentioning
confidence: 99%
“…Some incomplete sets of Yersinia effectors result increased macrophage death, either via YopE induction of pyroptosis (30, 31) or as a result of dysregulated effector and translocon secretion in the absence of YopK (32, 41). However, the ΔT3SE::+yopHEKM strain expresses both YopM, which prevents YopE-mediated activation of the pyrin inflammasome (30, 31), and YopK, which prevents inflammasome activation by translocon components (41, 42). As expected, therefore, this strain resulted in minimal macrophage death (Figure S1).…”
Section: Resultsmentioning
confidence: 99%